Banner of souls - Williams, Liz (New York : Bantam Books, 2004)
One of Mars's most elite warriors must travel to Earth, where she is assigned to guard a very special child. The girl's name is Lunae and is grown from a secret genetic code. She alone can breach time's barrier and alter the shape of things to come.
Keywords: Genetic engineering -- Fiction; Science fiction